An assessment of the level of women participation in public sector leadership and decision making: a case study of Kwekwe - Kufainyore, Fungai Christine (Midlands State University, 2018)
This study is a mixed approach which evaluated the participation of women in the public sector leadership and decision making in Kwekwe .Zimbabwe’s population rate has more women as compared to men with 51.27% women and men owning 48.73% of the population but only a few women are recognized in leadership and decision making in every sector. A review of why it is essential for women to participate was discussed and research was done to find out the number of women participating in leadership roles in Kwekwe’s public sector and whether they are given opportunities to make decisions. There are various challenges that were identified that made it hard for women to participate in leadership and decision making leading most of them to occupy middle posts .Questionnaires, interviews and documentary research were used as methods of collecting necessary information for the research. The study purposively sampled women in the public sector as well as males so as to get male perspective on the issue of women and participation. It also used selective sampling and selected residents in the city of Kwekwe to understand the society under research. The study found out that though there are conventions and systems that promote female representation patriarchy is still well established in the society as many males do not accept the view of women becoming leaders or earning more money than they do. Besides patriarchy women themselves have become their own enemies by creating hostility and hatred among themselves as the few that occupy leadership positions are not getting enough support from their female counterparts and women under other positions are complaining that women who become leaders do not seem to recognize their gender once they get in top management. Due to some of these reasons women have given men the opportunity to rise and obtain dominating roles as they lack unity and one voice. The study argues that there is need for the deconstruction of the mind and literature so as to socialize people on the importance of women participation, the need to promote democracy as well as getting rid of the patriarchal mentality. The eagerness for education should be available as well as the promotion of leadership courses ,awarding of women making a difference and focus groups for women to encourage them to come out of the closet.